2015
DOI: 10.1016/j.apenergy.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Why is the reliability of building simulation limited as a tool for evaluating energy conservation measures?

Abstract: Buildings account for approximately 32% of the total energy consumption globally and up to 40% in the developed countries, which makes buildings a prime target for energy conservation. Various energy conservation measures (ECMs) have been proposed to improve the energy efficiency in buildings, and these ECMs are usually designed and assessed using calibrated building energy models. However, there is empirical evidence that reveals noticeable discrepancies between simulated performances of ECMs reported in buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…However, many studies suggested that actual energy performances of buildings severely deviates from their original design conditions due to incorrect assumption or estimation of occupancy behavior [3][4][5][6]. Significant discrepancies have been observed [7,8] due to complicated interrelationship of energy consumption in building facilities and occupancy behavior [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies suggested that actual energy performances of buildings severely deviates from their original design conditions due to incorrect assumption or estimation of occupancy behavior [3][4][5][6]. Significant discrepancies have been observed [7,8] due to complicated interrelationship of energy consumption in building facilities and occupancy behavior [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A range of studies have shown individual case studies or evaluations of the results of many building energy simulations. While some carefully endorse simulation as being able to predict performance when models are accurately built [83], others show that uncalibrated simulations are often very far from representing reality and may not be useful tools for predicting performance [84], [85].…”
Section: Model Validation and Calibrationmentioning
confidence: 99%
“…Many studies have identified simulation as a good tool for building studies Ann 2002), such as its capability to evaluate the system performances when field experiments are infeasible and the investigation of various retrofitting solutions before being implemented. However, the reliability issue of using building energy models for assessing these solutions, especially the cross estimation between different solutions, has been well noticed in previous study (Li et al 2015). While all the retrofitting solution are simulated based on the calibrated base case, there is lack of possible and available data to calibrate the model after applied each solutions.…”
Section: Utilizability Of Combined Scenariosmentioning
confidence: 99%